Nonliner mechanism of electromagnetic waves generations in space dust plasma - Voitsekhovskа, A.D.; Yukhimuk, A.K.; Sirenko, O.K. (Вопросы атомной науки и техники, 2007)
We consider a parametric excitation of electromagnetic waves induced by inertial Alfvén wave (IAW) in space dust plasma. The nonlinear dispersion equations describing decay of upper-hybrid wave (UHW) into the IAW and the ordinary electromagnetic wave as well as decay of UNW into the IAW and the left-hand circularly polarized (LHCP) wave are obtained using the three-fluid magnetohydrodynamics. The instability growth rates which depend on dust plasma parameters are found. It is shown that the LPCH wave is preferably excited by the UH pump wave for the parameters of the Saturn's F-ring.